Leadership in Esports Teams: A Model on Leader-Member Exchange, Organizational Loyalty, and Task Performance Concepts - Orçun Keçeci; Veli Onur Çelik (SAGE Open)
Leadership is an age-old phenomenon that coexists with human history, yet constantly transforming in line with the needs of the times. Accordingly, leadership is a subject that needs to be examined in the context of esports, the popular sport of the modern era. In the literature, studies that explore the concepts of esports and leadership together do not directly focus on the leadership of team coaches and the impact of these leadership processes on other concepts. In this context, the study aims to reveal the components of leadership in esports according to players’ perceptions and to test whether a model can be formed along with the concepts of leader-member exchange, organizational loyalty, and task performance. In this direction, research based on a mixed-method approach has been designed. The research predominantly consists of quantitative methods. The qualitative phase serves as a preliminary stage to initiate the quantitative phase. In this regard, it is a study based on an exploratory pattern within mixed methods. The research population consists of professional esports players playing in Turkish teams. Firstly, the Esports Leadership Scale was developed to determine the components of leadership in esports. After that, the validity of the envisaged research model was tested through the structural equation model. As a result of the analyses, it was found that the effect values related to the envisaged model were significant. This result shows that esports leadership can impact leader-member exchange, organizational loyalty, and task performance.